2015
DOI: 10.1039/c4ra16365f
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed green synthesis of enantiopure atenolol

Abstract: A new green route is proposed for the synthesis of enantiopure atenolol (a β1-blocker).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Most of the employed enzymes were found converting both the atenolol enantiomers. Although a previous study found that the immobilized CALB is a prospective enzyme, the enzyme changed both atenolol enantiomers as most other biocatalysts. Previously, lipase PS immobilized on diatomite earth (lipase PS‐D) had successfully catalyzed the kinetic resolution of the racemic atenolol, but the free‐form lipase Amano PS from Burkholderia cepacia used in the experiments was not able to resolve the compound.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Most of the employed enzymes were found converting both the atenolol enantiomers. Although a previous study found that the immobilized CALB is a prospective enzyme, the enzyme changed both atenolol enantiomers as most other biocatalysts. Previously, lipase PS immobilized on diatomite earth (lipase PS‐D) had successfully catalyzed the kinetic resolution of the racemic atenolol, but the free‐form lipase Amano PS from Burkholderia cepacia used in the experiments was not able to resolve the compound.…”
Section: Resultsmentioning
confidence: 90%
“…The second method resolves the available racemic atenolol via chromatographic resolutions, which employ many types of chiral selectors, microbial fermentation of the racemate or its derivative, and enantioselective esterification or hydrolysis of the racemate using immobilized enzymes . Recently, formation of the enantiomer was offered through an enzymatic transesterification reaction of a racemic alcohol, precursor of the ( S )‐atenolol, in ionic liquids . Since the racemic atenolol is available in markets, the kinetic resolution is the faster strategy to produce the single enantiomer than asymmetric syntheses …”
Section: Introductionmentioning
confidence: 99%
“…Chiral HPLC and optical rotation analysis was used to determine the optical purity of synthesized compounds. Here, the nucleophilic ring opening of oxirane at the least substituted carbon atom followed by nucleophilic displacement of chlorine atom through S N (concerted) mechanism (Scheme ) may have been responsible for the inversion of configuration . Following the same mechanism, ( R )‐ 11 can be prepared from ( S )‐ 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the two enantiomers of b-blockers feature the same chemical and physical properties in an achiral environment, they differ in pharmacological activity. It has been reported by many studies that only the S-enantiomer of b-blockers has the desired therapeutic effect, whereas the administration of the racemate may cause dangerous side effects, such as bronchoconstriction or diabetes (6)(7)(8)(9). Nevertheless, b-blockers are still commercially available and mainly used in medicine as racemates.…”
Section: Introductionmentioning
confidence: 99%